Who uses technical aids in old age? Exploring the implementation of technology-based home modifications in Europe - Schmidt, Laura I.; Wagner, Melanie; Büßecker, Hanna A.; Franke, Annette A. (Frontiers in Public Health, 2023)
Introduction Home modifications and features, e.g., handrails or ramps for people using wheelchairs, should allow residents with functional limitations to maintain social participation, health, and wellbeing for aging in place. However, there is little evidence in relation to the individual characteristics shaping this implementation of technology-based home modifications. Current studies often focus on describing the distribution of certain implementations in households but do not provide information on factors predicting the implementation or detailed and multifaceted data on associations with characteristics of the older user. This article, therefore, examines the use of well-established technological aids and home modifications (e.g., ramps, handrails, automatic doors, bathroom or kitchen modifications, chair lifts, and alerting devices) in the households of older adults in Europe. We refer to Lawton's and Nahemow's concept of personal-environment fit and describe the use of technical aids across 18 countries, analyze associations with individual characteristics and social resources, and compare those associations and variance explanation between older adults in their third age (“young-old”, 65–79 years) and older adults in their fourth age (“old-old”, 80+). Methods Drawing on representative data from the Survey of Health, Ageing, and Retirement in Europe (SHARE), wave 6, a total of N = 38,553 older adults aged 65–105 years (M = 74.4 years, SD = 7.1; 55% women) were analyzed by performing hierarchical logistic regression analyses. Results Indicators of functioning explained the highest proportion of variance, followed by social resources, and variance explanation was higher for the fourth age than for the third age. In particular, older adults with physical limitations, a larger social network, and those who received care from a child outside the household were more likely to have home modifications installed. Discussion The study provides an overview of associations of diverse variables with assistive devices and modifications in the home and can serve as a starting point for public health activities concerning the heterogeneity of people aged 65 years and older.